CITREX UMP showcases 279 students and researchers innovative products - Mimi Rabita, Abdul Wahit (2023)
GAMBANG, 14 March 2023 - The 13th Creation, Innovation, Technology & Research Exposition (CITREX), Universiti Malaysia Pahang (UMP) 2023 exhibition saw 84 gold medalists, 146 silver medallists and 36 bronze medallists with 279 entries from staff, IPT students and school students.